‘There is no place for you here’: a phenomenological study of exclusion - Mladenov, Teodor (Critical Disability Discourses, 2012)
On the 19th of July, 2008, a group of young disabled visitors (wheelchair users) were expelled from the Troyan Monastery in Bulgaria by the hegumen of the monastery with the stipulation that ‘obviously you pay for others’ sins, since you are like this’. Two years later the Bulgarian Commission for the Protection against Discrimination found the hegumen guilty of harassment on the basis of disability. In this paper I analyse the Commission’s decision from a phenomenological perspective. I draw on Heidegger’s existential phenomenology and also on concepts borrowed from the domain of Science and Technology Studies. I explore the existential-ontological patterns that are implicitly at work in the event as recounted in the Commission’s decision. Thus, a spatio-temporal distribution of human beings according to a rigid interiority/exteriority logic is identified. This spatio-temporal pattern is informed by an understanding of space that prioritizes proximity, and by an understanding of time that prioritizes permanence. The interiority/exteriority division, on its behalf, is sustained by a highly contested ‘boundary-work’, in which different non-human entities are recruited as mediators. Keywords: disability, discrimination, phenomenology, boundary-work, science and technology Studies